Ethyl acetate fraction from methanol extraction of Vitis thunbergii var. taiwaniana induced G0/G1 phase arrest via inhibition of cyclins D and E and induction of apoptosis through caspase‐dependent and ‐independent pathways in human prostate carcinoma DU145 cells. Issue 1 (22nd September 2017) - Lin, Chia‐Hsin; Chan, Hsiao‐Sung; Tsay, Hsin‐Sheng; Funayama, Shinji; Kuo, Chao‐Lin; Chung, Jing‐Gung
Abstract: Vitis thunbergii var. taiwaniana (VTT) is a wild grape native to Taiwan, belonging to the Vitaceae family and Vitis genus, and widely used as folk herbal medicine. It is traditionally used for the treatment of diarrhea, hypertension, neuroprotection, jaundice, and arthritis. We used the wild‐collected VTT and sterilized them to establish the plant tissue culture, and then took the leaves for DNA sequencing to determine its original base. We use methanol to extract VTT in four different solvents: 1‐butanol, n ‐hexane, ethyl acetate, and water. These four preliminary extracts were used to treat human prostate cancer DU145 cells in vitro. We use the flow cytometry to check the cell survival situation. Finally, we found the ethyl acetate layer roughing product (referred VTEA) in human prostate cancer apoptotic effects of cell line DU‐145. In the present studies, we use the crude extract of VTT to examine whether or not it can induce apoptosis of DU145 cells in vitro. Viability assays for extracts of VTT treatment showed that it had dose‐dependent effect on human prostate cancer DU145 cells. We also found that the extract of VTT induces time‐dependent mitochondrial and intrinsic‐dependent apoptosis pathways. The in vitro cytotoxic effects were investigated by cell cycle analysis and the determination of apoptotic DNA fragmentation in DU145 cells. The cell cycle analysis showed that extracts of VTT induced a significant increase in the number of cells in G 0 / G 1 phase. The extract of VTT induced chromatin changes and apoptosis of DU145 cells also were confirmed by DAPI and PI staining that were measured by fluorescence microscopy and flow cytometry, respectively. Finally, the expression of relevant proteins was analyzed by Western blot analysis. These results promoted us to further evaluate apoptosis associated proteins and elucidate the possible signal pathway in DU‐145 cells after treated with the extract of VTT.